Penanganan Stunting di Provinsi Sumatera Barat dalam Perspektif Sound Governance - Fajar Noor Ramadhian; Indah Adi Putri; Ria Ariany; Roni Ekha Putera (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Even though the SSGI stunting rate decreased from 24.4% in 2021 to 21.6% in 2022, West Sumatra province is one of the provinces in Indonesia with a fairly high stunting rate. One of the cities in West Sumatra which is the largest producer of animal and vegetable food is the city of Padang Panjang. The potential of Padang Panjang City is expected to be able to support the development of the younger generation optimally. However, ironically, around 19% of teenagers still suffered from malnutrition and stunting in Padang Panjang City in 2018. Apart from that, the third area in West Sumatra Province that was designated by Bappenas as a place to care for stunted children, namely Solok Regency. This research uses the concept/theory of good governance according to Ali Farazmand. This research uses a literature review method. This research produces an analysis of the existence of inclusive policies to support the accessibility of district/city areas which have an impact on the potential for economic prosperity. Furthermore, this becomes the axis of health and nutrition development. Finally, there should be policies that produce international synergy in the use of agricultural and fisheries resources which have an influence on the development of health and nutrition in the region.